Komunikasi Pemasaran Terpadu dalam Membidik Pasar Pembaca Muda - Efendi, Gina Faleri (UPT Publikasi Ilmiah UNISBA, 2023)
Abstract. Daily mail of Kedaulatan Rakyat (KR) is the oldest local daily mail in Yogyakarta. The stigma of society has assumes that daily mail is far from daily modern and less update so it’s just read by older people. In addition, the interest of reading daily mail of the young generation has begun to decline. To change the stigma of the community and increase the reading interest, The daily of KR provides space for young readers by creating a rubric devoted to the young generation with Kaca rubric and Swara Kampus rubric. This study head for to determine integrated marketing communication daily mail of KR in targeting the reader market in expanding the young reader market. This research uses qualitative research methods with descriptive case study approach through data collection techniques to obtain data in depth. The result of this research is daily mail of KR has not been able to expand the young reader market as significantly, because the digital media is more powerful than newspaper, but through Kaca and Swara Kampus rubrics have been quite successful in increasing the reading interest of the young generation and construct that daily mail of KR is one of the reference newspapers that worth reading by young people in Yogyakarta.